Innovation, Resiliency, and Genius in Intensive English Programs: Decolonializing Recruitment and Contradictory Advocacy. (19th March 2021) - Litzenberg, Jason
Abstract: This article considers Intensive English Programs (IEPs) affiliated with higher education institutions of the Global North from the perspective of a decolonial option in which English is viewed as a tool of modernity used for colonization and the maintenance of unequal socioeconomic and power structures. Via nuanced description (Pennycook and Makoni 2020 ) of two colonizing practices typical to IEPs—namely, recruitment and advocacy—the article argues that the traits of resiliency, innovation, and genius commonly ascribed to IEPs are qualities that lend themselves to the refoundation, reconfiguration, and reconstruction (de Sousa Santos 2019 ) of alternative visions. In this way, IEPs have the opportunity to promote the liberatory visions of applied linguistics' practitioners and to positively influence decolonialization of the field. Because of their historical involvement in English language teaching and the industry it has spawned, applied linguists have an obligation to foster these changes, which need not affect the ability of IEPs to conduct language pedagogy or to provide the field with opportunities for research, teacher training, and professional development.